Vozes de mulher em Moçambique: Hirondina Joshua e “Os ângulos da casa” - Costa, Sayonara Souza da (2022)
The present research aims to raise discussions in relation to literature by women in Mozambique, as well as to disseminate names of women who write in this country. The objectives are based on verifying the aesthetic and ideological processes that frame these productions and how they face the difficulties that permeate a patriarchal society, which had its initial landmark in literature still late, because of the Portuguese colonization process. In this way, the analyzes of the first seven poems of the book will be made; checking the themes that arise, as well as the figure of the house and the symbology of the numbers that represent the titles of the texts. The writing style, the question of subjectivity and metaphysics are also elements that will be verified throughout the research. The relevance of this study is to give space to the new voices of Mozambican writers, so that their writings are highlighted and their concerns are open to new readings. The corpus used is the book Ângulos da casa (2016), by writer Hirondina Joshua. The book was published in Mozambique in 2016 and in Brazil in 2017. Some observations will be made throughout the writing, the issue of female authorship, as already mentioned, is one of them, asthere is still a great problem involving this issue. Therefore, the research was developed in three stages: the first chapter deals with the issue of female authorship in Mozambique, through a historical overview related to the precursor, mother of Mozambican poets, Noémia de Sousa, until we reach the contemporary authors: Sónia Sultuane , Tania Tomé and Rinkel. The second chapter is dedicated to Hirondina Joshua, her place in the literature of her country and the question of introspection present in her poems. The third chapter is composed of the theoretical discussion in relation to space, the house, the symbology of numbers until, in fact, we enter the analysis of the first seven poems that make up the Ângulos da casa (2016). Once this is done, we will have a clearer picture of how the process of female authorship is built in Mozambique and how these women's voices have sought their places as writers. Thus, we will conclude with the analysis of Joshua's poetry, within the established framework, and the literary production of Mozambican female authorship from the perspective of writings that preceded it. For this, we will make use of theoretical concepts focused on the symbology of the house, using the foundations of Bachelard's (2008) poetics of spaces, which permeates the psychological study of physical places; Xavier's (2012) contribution regarding the house and positive or negative affective memories, as well as the historical question of Mozambican literature from the writings of Noa (2017). In addition to these, we will use the theoretical postulates of Chevalier (2009); Chiziane (2016); Almeida (2015), Borges Filho (2007), Brandão (2015), Compagnon (2010), Eagleton (2006), among others.